Cerebral Perfusion Patterns of Anxiety State in Patients With Pulmonary Nodules: A Study of Cerebral Blood Flow Based on Arterial Spin Labeling - Wang, Xiao-Hui; Liu, Xiao-Fan; Ao, Min; Wang, Ting; He, Jinglan; Gu, Yue-Wen; Fan, Jing-Wen; Yang, Li; Yu, Renqiang; Guo, Shuliang (Frontiers in Neuroscience, 2022)
Background and Purpose: Pulmonary nodules have become a non-negligible cause of anxiety, the mechanism of which is unclear. The study focus on the cerebral blood flow (CBF) of anxiety in patients with pulmonary nodules . Materials and Methods: Patients with unconfirmed pulmonary nodules were evaluated by Hamilton Anxiety Scale (HAMA). The total score > 14 was defined as anxiety group, and the total score ≤ 14 points was defined as non-anxiety group. A total of 38 patients were enrolled, of which 19 patients were the anxiety group and 19 were the non-anxiety group. All subjects underwent arterial spin labeling (ASL) imaging using a 3.0 T MRI. A two-sample t-test was performed to compare the CBF between the two groups. The CBF was extracted in brain regions with difference, and Spearman correlation was used to analyze the correlation between CBF and HAMA scores; ROC was used to analyze the performance of CBF to distinguish between the anxiety group and the non-anxiety group. Results: The CBF in the right insula/Heschl’s cortex of the anxiety group decreased (cluster = 109, peak t = 4.124, P < 0.001), and the CBF in the right postcentral gyrus increased (cluster = 53, peak t = −3.912, P < 0.001) in the anxiety group. But there was no correlation between CBF and HAMA score. The ROC analysis of the CBF of the right insula/Heschl’s cortex showed that the AUC was 0.856 (95%CI, 0.729, 0.983; P < 0.001), the optimal cutoff value of the CBF was 50.899, with the sensitivity of 0.895, and specificity of 0.789. The ROC analysis of CBF in the right postcentral gyrus showed that the AUC was 0.845 (95%CI, 0.718, 0.972; P < 0.001), the optimal cutoff value of CBF was 43.595, with the sensitivity of 0.737, and specificity of 0.842. Conclusions: The CBF of the right insula/Heschl’s cortex decreased and the CBF of the right postcentral gyrus increased in patients with pulmonary nodules under anxiety state, and the CBF of the aforementioned brain regions can accurately distinguish the anxiety group from the non-anxiety group.